2001
DOI: 10.1055/s-2001-17205
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-Amphetamine-Regulated Transcript Influences Energy Metabolism, Anxiety and Gastric Emptying in Mice

Abstract: This study was designed to investigate the effects of cocaine-amphetamine-regulated transcript (CART), a recently discovered hypothalamic neuropeptide, on food intake, anxiety, oxygen consumption and gastric emptying in mice. Intracerebroventricular (i. c. v.) injection of CART (1 - 100 pmol) markedly reduced food intake in a dose-related manner. A significant decrease was observed 20 min after i. c. v. injection of CART and continued for four hours. In the elevated plus maze test, i. c. v. CART injection sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…We also showed that atropine blocked the 2 nmol/rat ghrelin dose effect on gastric emptying and intestinal transit, suggesting that the prokinetic effect of ghrelin was mediated via the cholinergic pathway. This result is consistent with previous reports (20,27) in which the prokinetic effect of ghrelin was dependent on an intact vagal function (2) and that atropine and/or vagotomy blocked the effect of ghrelin on gastric (27) and intestinal motility (13) in rats. Other mechanisms involve tachykininergic pathways, as demonstrated in the electrical field stimulation studies in isolated rat stomach (3).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We also showed that atropine blocked the 2 nmol/rat ghrelin dose effect on gastric emptying and intestinal transit, suggesting that the prokinetic effect of ghrelin was mediated via the cholinergic pathway. This result is consistent with previous reports (20,27) in which the prokinetic effect of ghrelin was dependent on an intact vagal function (2) and that atropine and/or vagotomy blocked the effect of ghrelin on gastric (27) and intestinal motility (13) in rats. Other mechanisms involve tachykininergic pathways, as demonstrated in the electrical field stimulation studies in isolated rat stomach (3).…”
Section: Discussionsupporting
confidence: 83%
“…Ghrelin is known to possess prokinetic characteristics. In healthy mice, ghrelin increased gastric emptying (2,20,23,40). In healthy rats, ghrelin also improved gastric emptying (9,15,25,37), increased the frequency of migrating Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In support of this concept is the recent identification of a polymorphism in intron 1 of the CART gene that is associated with alcoholism in the Korean male population (Jung et al, 2004). CART also plays an important role in anxiety-like behavior and stress-related responses (Chaki et al, 2003;Stanek, 2006), and dosedependently enhances anxiety-like behavior in the elevated plus maze (EPM) test in both rats (Kask et al, 2000) and mice (Asakawa et al, 2001).…”
Section: Introductionmentioning
confidence: 71%
“…Several studies have suggested an important role of CART in anxiety-like behavior (Kask et al, 2000;Asakawa et al, 2001;Chaki et al, 2003). Administration of icv to rats results in a decreased ratio of open/total arm entries and reduces time spent in open part of the maze, thus suggesting increased anxiety-like behavior (Kask et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies would suggest a decreased metabolic efficiency after intrahypothalamic or intracerebroventricular CART administration to normal or obese rats, indicated by increased expression of uncoupling proteins 1, 2, and 3 in brown and white adipose tissue or muscle (Wang et al, 2000), increased lipid oxidation , a higher thermogenic response to a β3 agonist, increased uncoupling protein-1 mRNA expression in brown adipose tissue and significantly greater weight loss in response to 24-h fasting (Kong et al, 2003). Another study, however, has suggested that intracerebroventricular CART administration reduces metabolic rate, as indicated by a decrease in oxygen consumption (Asakawa et al, 2001), but this effect may be related to the fact that CART, particularly in higher doses and when administered intracerebroventricular but not intrahypothalamically, induces motor disturbances (Larsen et al, 2000 andAbbott et al, 2001) which could inhibit food intake, physical activity and metabolic rate.…”
Section: Effects Of Hypothalamic Regulators Of Energy Balance On Enermentioning
confidence: 96%